NIR-responsive carbon dots for efficient photothermal cancer therapy at low power densities. (August 2018) - Geng, Bijiang; Yang, Dewen; Pan, Dengyu; Wang, Liang; Zheng, Fengfeng; Shen, Wenwen; Zhang, Chen; Li, Xiaokai
Abstract: Carbon dots (CDs) with unique optical properties are a stable and highly biocompatible fluorescent material offering enormous application potential in optical imaging and photothermal cancer therapy (PTT). However, the low photothermal conversion efficiency and the high power density still impede the development of CDs in PTT. Herein, the nitrogen and oxygen co-doped CDs (N-O-CDs) with strong absorbance in the near infrared (NIR) region were prepared from 1, 3, 6-trinitropyrene (TNP) and N-containing polymer of branched polyethylenimine (BPEI) via a one-step molecular fusion route. The as-prepared black N-O-CDs with high photostability and superb biocompatibility can be utilized not only as a new fluorescence imaging agent but also as an excellent PTT agent in vivo . The structure, optical properties, bioimaging, photothermal effect in vitro, and therapeutic efficiency in vivo of the N-O-CDs are investigated. The low power density (0.8 W cm −2 ) and high photothermal conversion efficiency (η = 38.3%) facilitate N-O-CDs to act as an ideal theranostic agent for fluorescence imaging and photothermal therapy in vitro and in vivo . This work highlights CDs as an excellent candidate for efficient cancer therapy. Graphical abstract: Image 1